The Impact of Rumen-Protected L-Arginine Oral Supplementation on Libido, Semen Quality, Reproductive Organ Biometry, and Serum Biochemical Parameters of Rams - Hussein, Hassan A.; Hassaneen, Ahmed S. A.; Ali, Montaser E.; Sindi, Ramya A.; Ashour, Abdallah M.; Fahmy, Salem M.; Swelum, Ayman A.; Ahmed, Ahmed E. (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effect of oral supplementation of rumen-protected L-arginine on semen quality, testes and accessory genital glands biometry in rams. Ten apparently healthy and fertile rams were randomly divided into two equal groups; control, and rumen-protected L-arginine (20 Mg/Kg body weight for 30 days) treated group. In all rams, ultrasonographic measurements of the testes and the accessory genital glands and blood sampling were performed at day (D)10, D20, and D30 (D0 is the start of supplementation). Semen ejaculates were collected twice/week and semen quantity, and quality were examined. Our results showed that, in the L-arginine treated group, there were significant increase in the ultrasound biometric measurement of right seminal vesicle (RSV) and right Cowper’s gland (RCG) at D10, both testes, tail of the epididymis (TE), SV and CG of both sides at D20, and of both testes, RTE, RSV, RCG, and LSV at D30. Semen quality and quantity parameters were significantly improved in L-arginine treated group. Moreover, testosterone level in the L-arginine treated group was significantly higher than that in the Control group. Serum thyroxine and glutathione peroxidase concentrations were significantly higher in the L-arginine treated group. The present study concluded that oral supplementation with rumen-protected L-arginine is beneficial in improvement of rams’ fertility.